Monstruologia : Vida y milagros of los espeluznantes, los repugnantes 7 los muertos vivientes - Slade, Arthur G. (Scholastic, 2007)
Monsterology: Fabulous Lives of the Creepy, the Revolting, and the Undead is themost fun anyone can have with some of the nastiest creatures ever imagine! Who can resist morsels like the fact that "Drakul" mean "son of the dragon" in Romanian, that the first Golem may have been Enkidu, who appeared inthe ancient Epic of Gilgamesh, and that Frankenstein's Monster was first inpsired by Mary Shelley's nightmare? Governor General's Award-winner Arthur Slade has gathered together fifteen scary critters, ranging from Dracula to Golem, from Frankenstein to Baba Yaga and even a zombie. He provides facts, real history, imagined history, and lots of jokes to make these creatures come to life. Slade's hilarious text presents delicious imagined gossip, favorite blook types, favorite movies, and even favorite haunts (you shou8ld pardon the expression) with character descriptions and thoroughly researched background information. Lively black-and-white illustrations by Derek mah make this a book that is sure to be a hit with every monster-loving reader.